PERSEPSI PARA PENDIDIK TERHADAP TANTANGAN – TANTANGAN DALAM PENGAJARAN BAHASA INGGRIS - Hafizah Rifiyanti; Maola Nurtika; Sri Rahayu; Iis Nurhayati (PT. Jurnal Center Indonesia Publisher, 2024)
This study aims to explore teachers' perceptions of challenges in English language teaching and the strategies they use to overcome these challenges. This study used a qualitative approach with a judgement sampling method. The participants selected were 23 teachers who teach English at all levels of education, ranging from primary school to university. The data was collected through a survey distributed using google form, the survey was conducted to gather the experiences, and opinions of the teachers regarding the challenges they face in teaching English. The results showed that the different ability levels of students, time constraints, availability of teaching resources, and the perception of English as a foreign language were the main challenges faced by the teachers. To overcome these challenges, teachers use various strategies, including attending training and seminars, using technology in teaching, and conducting continuous evaluation and assessment. In addition, collaboration among teachers and increased professional training are also considered important in overcoming challenges in English language teaching. The findings provide valuable insights for the development of more effective strategies and policies to improve the quality of English language teaching in schools.